PERAN PENYULUH DALAM AGRIBISNIS PERIKANAN AIR PAYAU DI KABUPATEN BANGKALAN MADURA - Hurrul Fikri; Sri Subekti; Sofia Sofia (University of Jember, 2017)
Vaname household agri-fishery (RTVE) is a vaname shrimp farming activity undertaken in pool tarps. One of shrimp farmers, who are successful in this business and are now being self-help instructors in collaboration with the government owned fishing instructors to promote these activities, are the shrimp farmers in Kwanyar Sub-district of Bangkalan. This research was aimed to explain : (1) the implementation of extension practices in Vaname Fisheries, (2) the role of extension agents, and (3) the problems during extension practices. This research used qualitative method by using the data analysis model proposed by Miles and Huberman. The results shows : (1) There are differences on extension implementation between PNS and self-help-instructor agents. Equipments, evaluation system, and extension methods are the different aspects of extension implementation. (2) the PNS agents have an optimal role as an instructor and analyst. However, the self-help instructor has an optimal role as instrutor, facilitator, motivator, advisor, surveyor and organizer. (3) the obstacle and problems which were faced by PNS and self-help-instructor are also different. PNS extension agents have much problems in technical terms such as distance, time, facility, extension agents and knowledge problems. Otherwise, self-help-instrucor faced problems especially in human error and outside interventionKeywords: Instructors, Shrimp farmers, Vaname household agri-fishery (RTVE)